Body mass index has a non-linear association with three-month outcomes in men with acute ischemic stroke: An analysis based on data from a prospective cohort study - Zan, Yibing; Xiong, Wei; Zhang, Xiaohua; Han, Yong; Cao, Changchun; Hu, Haofei; Wang, Yulong; Ou, Haining (Frontiers in Endocrinology, 2022)
Objective: Despite reports of a connection between body mass index (BMI) and stroke outcome, the findings remain debatable. In this investigation, we sought to determine whether BMI was associated with the probability of 3-month unfavorable outcomes in patients with acute ischemic stroke (AIS). Methods: This is a second analysis based on a cohort study. 1,897 people with AIS who were treated at a hospital in South Korea from January 2010 to December 2016 were included in the study. The linear relationship between BMI and unfavorable outcomes for AIS patients was evaluated using a binary logistic regression model. The generalized additive model (GAM) and smoothed curve fitting (penalized spline approach) were employed to see if there was a non-linear association between BMI and unfavorable outcomes in patients with AIS. Results： The binary logistic regression model did not detect any statistically significant correlation between BMI and unfavorable outcomes in AIS patients after controlling for variables. The association between them, however, was non-linear, with the BMI inflection point occurring at 23.07 kg/m2. Each 1 kg/m2 rise in BMI on the left side of the inflection point was linked to a 12% lower risk of unfavorable outcomes (OR= 0.88, 95% CI: 0.82 to 0.96, p = 0.003). We stratified the AIS patients by gender to further explore their relationship. The results showed a specific non-linear relationship and saturation effect of BMI (kg/m2) with 3-month unfavorable outcomes in male patients but not in female patients. The inflection point for BMI was 23.35 kg/m2. When BMI was below 23.35 kg/m2 in men with AIS, BMI was inversely associated with unfavorable outcomes (OR=0.89,95% CI:0.80-0.98). Conclusion: A particular non-linear connection and saturation effect between BMI (kg/m2) and 3-month unfavorable outcomes were present in male patients with AIS but not in females. 23.35 kg/m2 was the BMI's inflection point. The probability of unfavorable outcomes was substantially and inversely associated with BMI in men with AIS when it was less than 23.35 kg/m2. Men with AIS should have a BMI of no less than 23.35 kg/m2 to reduce the probability of unfavorable outcomes following AIS.